TINGKAT KETERAMPILAN DASAR SHOOTING, DRIBBLING DAN PASSING PADA EKSTRAKURIKULER BOLA BASKET SISWA PUTRA SMP NEGERI 4 JOMBANG - Arif Kustoro; Garnika Ade Sinto Raya (Dharmas Journal of Sport, 2023)
The basic technique of basketball is a very important technique in the running of a basketball game or match. Some of the basic techniques applied in junior high school level learning are dribbling, shooting, and passing. This study aims to determine the level of basic skills in playing basketball. The targets in this study were 32 boys' basketball extracurricular students at SMP Negeri 4 Jombang. The type of research used is quantitative with a survey method. The test instrument used the Johson Basketball test with a validity test of 0.79 and a reliability test of 0.80. Data were processed using descriptive statistical analysis techniques with SPSS 22.0 series. The results of the research on the basic skill level of playing basketball for male students who take part in extracurricular activities at SMP Negeri 4 Jombang show that there are 3 students (9.4%) in the very good category, 6 students (18.8%) in the good category, 12 students (37.5%) in the moderate category. %), in the less category there are 8 students (25%), and in the very less category there are 3 students (9.4%).